The Issue of Unconscious Bias in Referee Decisions in the National Rugby League - O'Brien, Katherine A.; Mangan, John (Frontiers in Sports and Active Living, 2021)
Referees are appointed to be impartial sporting figures. They are trained to provide leadership and guidance, interpret infractions, adjudicate rules, all while maintaining the highest levels of objectivity and sense (Hancock, Martin, Evans, & Paradis, 2018; Lirgg, Feltz, & Merrie, 2016). However, when decisions are driven by individual heuristics, limited information, context, goal motivations, emotions, time pressures and cognitive load (Hill & Windmann, 2014; Osório, 2020), it can be difficult to discern how and why particular referee judgements are made. In this paper, we draw on data from the major Rugby League competition in Australia between the years 1978 to 2019 to examine whether clubs fare significantly better or worse under particular National Rugby League referees. We examine potential causes that might contribute to the referee effect and ask why, after years of specialist training and game assessments, are rugby league referees, even at the elite professional level, still processing information in preferential ways.